Automated Sample Combustion and CO2 Collection System with IRMS for 14C AMS in Yamagata University, Japan. Issue 1 (2014) - Kato, Kazuhiro; Tokanai, Fuyuki; Anshita, Minoru; Sakurai, Hirohisa; Ohashi, Mami S
Abstract : Accelerator mass spectrometry (AMS) was introduced at Yamagata University in 2010, including the measurement of radiocarbon. In the Yamagata University laboratory (YU-AMS), the application of 14 C AMS is aimed at microdose pharmacokinetics investigation and the development of improved sample preparation techniques. The lab also measures environmental samples. With the installation of this AMS system, a new automated sample production system was installed, which is composed of an elemental analyzer, a glass vacuum line, and an isotope ratio mass spectrometer (IRMS). In this system, it is also possible to measure stable isotopes (δ 13 C, δ 15 N, and δ 34 S) of the sample gas using a mass spectrometer. To increase the amount of CO2 gas introduced into the glass vacuum line, the gas mass flow introduced into the MS was reduced, and the change of δ 13 C accompanying this reduction was monitored. The sample gas split was changed to set the glass vacuum line (GVL):isotope ratio mass spectrometer (IRMS) ratio to 5:5, 8:2, and 9:1, and δ 13 C was measured for each ratio. It was confirmed that there was no effect on the isotopic fractionation accompanying the change in the sample gas split ratio. To prioritize the use of gas in the production of graphite, the GVL:IRMS ratio of 9:1 was chosen for this setup. The components are connected on-line, and up to 20 samples can be processed automatically.